4x+9=7x-3

Simple and best practice solution for 4x+9=7x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+9=7x-3 equation:


Simplifying
4x + 9 = 7x + -3

Reorder the terms:
9 + 4x = 7x + -3

Reorder the terms:
9 + 4x = -3 + 7x

Solving
9 + 4x = -3 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
9 + 4x + -7x = -3 + 7x + -7x

Combine like terms: 4x + -7x = -3x
9 + -3x = -3 + 7x + -7x

Combine like terms: 7x + -7x = 0
9 + -3x = -3 + 0
9 + -3x = -3

Add '-9' to each side of the equation.
9 + -9 + -3x = -3 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = -3 + -9
-3x = -3 + -9

Combine like terms: -3 + -9 = -12
-3x = -12

Divide each side by '-3'.
x = 4

Simplifying
x = 4

See similar equations:

| 7x-11+3x=-37 | | 33.7=g-40.48 | | 2x+13/2=68 | | 3a=7-a | | 3a=7-a | | 3a=7-a | | 5d+18d-4r-7r= | | (2x^2+3x-4)x(2x-3)= | | 2(3-x)=9(x-7) | | 100,000+x+x=600,000,000 | | -x-3=-3 | | 7+3t=-t/8 | | 6x+19=15x-90 | | 5.5w-36=w | | 2x-4=-4x+16 | | 5(16)+8y=40 | | 5x-3=-6x-10 | | -[9x-(6x+4)]=10-(5x-2) | | 6=-S(X+2) | | 25g=2g+(-288)+5g | | -10x-(-40)=-50 | | 5x^2-18x+16=0 | | 5x+8=4x-3 | | (x+1)x(4x^2-4x+9)= | | m=-7+13a | | (14+x)+x=346 | | -12x-24=36 | | 9x-(4x+6)=24 | | 7+2x(y+3)= | | 5g^8+25g^5-20g^3= | | 16w^3-25w=0 | | N+12=38 |

Equations solver categories